Simultaneous determination of indapamide, perindopril and perindoprilat in human plasma or whole blood by UPLC-MS/MS and its pharmacokinetic application - Yi Tao; Sheng Wang; Lei Wang; Min Song; Taijun Hang (Elsevier, 2018)
Simple and sensitive methods were developed for the determination of indapamide, perindopril and its active metabolite perindoprilat in human plasma or whole blood by hyphenated ultra-performance liquid chromatography-mass spectrometry (UPLC-MS/MS). Indapamide-d3, perindopril-d4 and perindoprilat-d4 were used as the internal standards. The separation was performed on a Thermo BDS Hypersil C18 column (4.6 mm × 100 mm, 2.4 µm) for indapamide and perindopril simultaneously following a protein precipitation pretreatment of the biosamples. The separation of perindoprilat was achieved independently on a phenomenex PFP column (4.6 mm × 150 mm, 5 µm). All the analytes were quantitated with positive electrospray ionization and multiple reactions monitoring mode. The assay exhibited a linear range of 1-250 ng/mL for indapamide, 0.4-100 ng/mL for perindopril and 0.2-20 ng/mL for perindoprilat. The methods were fully validated to meet the requirements for bioassay in accuracy, precision, recovery, reproducibility, stabilities and matrix effects, and successfully applied to the pharmacokinetic study of perindopril tert-butylamine/indapamide compound tablets in Chinese healthy volunteers and the comparative pharmacokinetic study between plasma and whole blood. Keywords: Indapamide, Perindopril, Perindoprilat, Pharmacokinetics, LC-MS/MS